PENDAMPINGAN DALAM MEMANFAATKAN MEDIA PEMBELAJARAN OFFLINE DAN ONLINE DI DESA AEK NAJAJI - Rahmat Afandi Dongoran; FENY ASTUTI HASANAH; Nisa Amelia Siregar (Institut Pendidikan Tapanuli Selatan, 2022)
Online learning is internet assisted learning without face to face.Online learning has several weaknesses,including limited internet quota, children who are not comfortable studying at hame, limitad time for parents to accompany children to study,and so on which causes children not to focus on learnig. Parents play an important role.Especially in terms of prviding understanding to their children about the covid-19 outbreak, staying at home, and accompanying their children in learning. Like the people in aek najaji village, many prents’lack of understanding of children’s learning materials, and limited internet quota.Therefore, community service (PKM) aims to help children in learning by using online and offline learnig media. The method of implementing the activities includes the preparation stage(initial survey and problem identification), implementation stage (socialization and assistance in the use of online and offline learning media for 8 elementary school students and 2 junior high school! Students in Aek najaji village), stage program evaluation, and final reporting.The results obtained in this activity, the community in Aek Najaji village, elementary and junior high school student were helped in understanding the material taught by the teacher online.The use of onlineaand offline learning media increases the enthusiasm for learning because by using these media, they can immediately practice raktikum based learning activities, such as the use of caliper, screw micrometer, and the process of blowing almods using baking soda and vinegar.The follow up plan for this activity is a continuation of the PKM activities in the following year